EXPLORING THE PRACTICE OF HUMAN RESOURCE DEVELOPMENT IN FINNISH MUNICIPALITY ORGANIZATION: Case of Vaasa City Organization - Iqbal, Shadab (My University, 2013)
This qualitative study explored the practice of human resource development (HRD) in Vaasa city organization (VCO) including its five service organizations (Health, Social, Education, General administration and Technical services) to develop clear understanding of their HRD infrastructure and nature of activities occurring within them. The purpose was to produce HRD profile of a Vaasa city organization that clearly describe occurrence of activities related to all three functions of HRD described by Mclagan (1989); Training and Development, Organizational Development and Career Development. In addition, this study investigated the kind of challenges HRD professionals are facing in implementation of practices by identifying the major barriers to use HRD programs in VCO. Study posed a question to local HRD professionals to obtain key suggestions which can potentially lead to improve HRD in VCO to achieve performance, workforce capacity in attempt to deal with challenges related to human resources posed by changes in workforce demographics (e.g. work force aging and their continual mass retirements). HRD professionals described a potential role of HRD functions in integrating New Municipality Vision 2017 which aims to improve performance of local governments by increasing their financial and workforce efficiency to provide quality services to community. The conceptual framework of this study was based on contingency perspective of HRD proposed by Kuchinke (2003: 299). 12 HRD professionals were interviewed who were responsible for planning and organizing HRD activities in five different Service organizations (SOs) of Vaasa city. Qualitative data collected from respondents was used to advance empirical analysis, findings derived from analysis were used to answer all the research questions. The findings suggested that SOs were engaged differently in conducting range of HRD programs on regular basis. However, the HRD activities including planning process, nature and execution of those HRD activities reflected similarities among them in most cases. Interviewees from different SOs reported generic and specific occurrence of HRD activities by exhibiting a fairly comprehensive perspective towards some HRD practices while opportunistic approach towards others in Vaasa city organization. SOs indicated top three barriers to use and implement HRD programs, they ranked lack of integrated use of HRD functions as top barrier fallowed by llimited staff and expertise to conduct HRD activities second highest, these two were identified to be the most common barriers hindering the effective implementation of HRD programs. Overall suggestions given by HRD professional of different SOs to advance HRD practices in Vaasa city organization were linked to improve the management of HRD in service units. Due to pro-active workforce planning and city organization’s HRD policy being aligned with National HRD policy, SOs seem confident to effectively deal with challenges of workforces’ recruitment, training and development on large scale.
Keywords: Human Resource Development (HRD); Human Resource Professionals; Human Resource Development Practices; Vaasa City Organization (VCO); Service Organizations (SOs); fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|